An enhanced message verification system for vehicle-to-vehicle communication. (2018) - Limbasiya, Trupil; Das, Debasis
Smart vehicle plays a major role in today's technological universe and we have different vehicle applications with the help of the internet of things. To fulfil it, there is a requirement of expeditious communication along with integrity, availability, high delivery ratio and low overhead assets. Otherwise, specific information or data may be useless or there will be possibility of the serious problem(s). Vehicular communication is mostly preferable to transfer datagrams from one user to other applicants to accomplish these characteristics. However, the delivery of packets successfully is not a simple task and be familiar with the updated information due to various obstacles. Researchers suggested discrete protocols to procure different properties in this noisy vehicular ad-hoc network (VANET). Scientists designed systematic authentication models using user identity for vehicular technology. In this article, we investigate multiple vehicle communication algorithms. But, we find some vulnerabilities after performing analysis on the particular scheme. After that, we propose an enhanced authentication system focused on vehicle-to-vehicle data transmission to overcome the present flaws. In addition, the suggested protocol is protected against multiple attacks and efficient in terms of the execution.